2000
DOI: 10.1080/13557850050007374
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Body Weight Concerns and Weight Control Practices of 4th and 7th Grade Adolescents

Abstract: This study indicates that early in a child's sociocultural development, grade level, gender, race, and SES are influential in the perception of ideal adult body size and opposite gender ideal adult body size. These factors are also influential in determining concerns about weight and weight control practices. The findings of this study support the need to begin health and wellness education efforts early in childhood while taking into account racial, gender, age, and SES disparities. This knowledge can also be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
54
2
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 21 publications
5
54
2
3
Order By: Relevance
“…Além disso, nos jovens com nível socioeconômico mais elevado, foi verificada uma tendência de desejo por corpos mais magros e de uso de dietas (11,17) . Em estudos como o de Cok (14) , no qual o nível socioeconômico não foi fator associado a insatisfação com a imagem corporal, houve uma tendência de fatores como sexo (maior insatisfação para moças) e maturação (maior insatisfação para jovens mais maduros e mais velhos) se apresentarem como variáveis determinantes para a satisfação/insatisfação com a imagem corporal.…”
Section: Resultados E Análisesunclassified
See 1 more Smart Citation
“…Além disso, nos jovens com nível socioeconômico mais elevado, foi verificada uma tendência de desejo por corpos mais magros e de uso de dietas (11,17) . Em estudos como o de Cok (14) , no qual o nível socioeconômico não foi fator associado a insatisfação com a imagem corporal, houve uma tendência de fatores como sexo (maior insatisfação para moças) e maturação (maior insatisfação para jovens mais maduros e mais velhos) se apresentarem como variáveis determinantes para a satisfação/insatisfação com a imagem corporal.…”
Section: Resultados E Análisesunclassified
“…Adams et al (17) investigaram 1.597 jovens norte-americanas, escolares da educação básica, e identificaram que os jovens negros selecionaram um tamanho de corpo ideal significativamente maior do que os brancos, e mais jovens brancos relataram que estavam tentando perder peso em comparação aos negros. Um número maior de moças de nível socioeconô-mico alto estava tentando perder peso em relação às de baixo nível socioeconômico.…”
Section: Resultados E Análisesunclassified
“…For example, this study included only white children as participants and models, and thus our results reflect opinions of one racial group. Research has suggested that children who are black hold more accepting attitudes toward peers who are overweight; 26,35 and thus, more research with children in different racial groups is needed. Furthermore, it may be that our hypotheses were a better fit for children between 5 and 8 years of age, because they were closer in age to the models.…”
Section: Discussionmentioning
confidence: 99%
“…A large body of evidence has shown that body dissatisfaction is common among females all over the world (1)(2)(3)(4) . Asian countries report higher body dissatisfaction than Western countries (3,5) .…”
mentioning
confidence: 99%